Strategies to characterize Fungal lipase for application in Dairy industry and medicine - Ali, Sikander; Nasir, Aneeqa; Sajjad, Sidra; Siddique, Fizza (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Esters are synthesized by catalysis of lipolytic enzyme from fatty acids and glycerol. Lipases are extensively dispersed in the whole world, nevertheless merely lipolytic enzymes produced by microbes are significant commercially. The several uses of lipases includes hydrolysis of fats, taste enrichment in food treating, perseverance of racemic mixes and chemical evaluates etc. Lipases are used as analytical implements. Lipases are used in food industry as baking, brewing, dairy and cheese products formation, fruit juices, formation of syrup, starch production and especially in flavor production of cheese. They play an important part in curing, diagnosing, biochemical examination, and checking of several feared ailments. Lipases are used as indicator enzyme for medical purposes. Their increased or decreased level in the body show definite illness. They are used in drugs for diseases like Crohns disease, gastrointestinal disturbances cancer necrosis element and much more.